2020
DOI: 10.1111/jace.16984
|View full text |Cite
|
Sign up to set email alerts
|

A facile pathway to prepare molybdenum boride powder from molybdenum and boron carbide

Abstract: Molybdenum boride is an ideal hard and wear-resistant material. In this study, a new method is proposed for preparing molybdenum boride, by which Mo first reacts with B 4 C to generate the mixture of molybdenum boride and C, and then the product is decarburized by molten Ca to generate CaC 2 . Pure molybdenum boride could be obtained after acid leaching to remove the by-product CaC 2 . According to the experimental and thermodynamic calculation results, it is concluded that the single-phase MoB could be succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…When one increases the content of Mo up to ~8 % of weight the grain sizes of (Ti, Mo)B 2 and (Ti,Mo)C are reduced from ~100 to ~10 µm, while the coating hardness increases from 900 to 1,300 HV. One of the arguments confirming the possibility of the formation of molybdenum borides of various composition from the reaction mixture of Mo+B 4 C is given in work [15], which shows the fundamental possibility of obtaining a series of Mo x B y compounds by heating the Mo/B 4 C mixture over a temperature range of 1,273-1,673 K.…”
Section: Literature Review and Problem Statementmentioning
confidence: 88%
“…When one increases the content of Mo up to ~8 % of weight the grain sizes of (Ti, Mo)B 2 and (Ti,Mo)C are reduced from ~100 to ~10 µm, while the coating hardness increases from 900 to 1,300 HV. One of the arguments confirming the possibility of the formation of molybdenum borides of various composition from the reaction mixture of Mo+B 4 C is given in work [15], which shows the fundamental possibility of obtaining a series of Mo x B y compounds by heating the Mo/B 4 C mixture over a temperature range of 1,273-1,673 K.…”
Section: Literature Review and Problem Statementmentioning
confidence: 88%
“…can be synthesized by high temperature (>1200 K) and by high pressure (≈5.2 GPa) sintering ( Figure 4 a ). [ 4 , 17 , 34 ] It is reported that by annealing the varied mixture of B/Mo precursor (molar ratio: 0.5, 1.0. 2.5, 4, etc.)…”
Section: Synthesis Of Molybdenum Boridesmentioning
confidence: 99%
“…As a d‐block element with multiple oxidation states, molybdenum‐based borides show properties such as low cost, facile synthesis, structural diversity, high chemical stability, corrosion resistance, high hardness, and capability to replace precious metal catalysts. [ 17 , 18 , 19 , 20 ] Molybdenum‐based borides (molybdenum borides) are found in different stoichiometries and crystal structures namely α‐MoB, Mo 2 B, β‐MoB, α‐MoB 2 , β‐MoB 2 , Mo 2 B 4 , and Mo 2 B 5 , etc. [ 5 , 19 , 20 , 21 , 22 ] The abundant structures of Mo borides represent interesting chemical and mechanical properties which are established by the rearrangement and proportion of boron and molybdenum atoms in a unit cell.…”
Section: Introductionmentioning
confidence: 99%